2017
DOI: 10.1177/0961203317727602
|View full text |Cite
|
Sign up to set email alerts
|

Acute vision loss in systemic lupus erythematosus: bilateral combined retinal artery and vein occlusion as a catastrophic form of clinical flare

Abstract: Presentation of a combination of branch retinal artery occlusion (BRAO)/central retinal artery occlusion (CRAO) and central retinal vein occlusion (CRVO) in systemic lupus erythematosus (SLE) is extremely rare. Herein, we have presented the case of a 29-year-old female with SLE, who simultaneously developed bilateral CRVO and BRAO/CRAO in the absence of antiphospholipid syndrome (APS) as a catastrophic form of clinical flare. A combinatorial diagnosis of CRVO and BRAO/CRAO should be considered during clinical … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0
1

Year Published

2019
2019
2025
2025

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 18 publications
0
9
0
1
Order By: Relevance
“…The second patient with BRAO with evolving CRVO from the non-ischaemic type into the ischaemic variant, despite being on an aggressive treatment protocol, makes an interesting case study. Only eight cases of different combinations of the branch or BRAO/CRAO and CRVO, as an ophthalmic emergency, have been reported in SLE [5][6][7]14]. The exact pathogenesis of simultaneous BRAO/CRAO with CRVO in SLE remains unknown, but the hypercoagulable state is considered to be an essential factor.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The second patient with BRAO with evolving CRVO from the non-ischaemic type into the ischaemic variant, despite being on an aggressive treatment protocol, makes an interesting case study. Only eight cases of different combinations of the branch or BRAO/CRAO and CRVO, as an ophthalmic emergency, have been reported in SLE [5][6][7]14]. The exact pathogenesis of simultaneous BRAO/CRAO with CRVO in SLE remains unknown, but the hypercoagulable state is considered to be an essential factor.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, the common manifestations of retinopathy are cotton wool spots, retinal hemorrhages, and optic disc edema caused by chronic occlusive changes in small retinal arterioles [4]. Severe vaso-occlusive retinopathy in the combination form of branch retinal artery occlusion (BRAO)/central retinal artery occlusion (CRAO) with central retinal vein occlusion (CRVO) is rare, with only a few reported cases in the literature [5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…The degree or pattern of visual impairment is comparable to that of CRAO. Many reports have shown that CCRAVO frequently decreases visual acuity to FC and HM, or even to NLP [6, 12, 16, 17], but a few researchers have also shown that fairly good visual acuity can be maintained [10, 1820]. In Brown's study [12], 87% (20/23) of eyes with CCRAVO had visual acuity between FC and NLP.…”
Section: Discussionmentioning
confidence: 99%
“…Adicionalmente, su unión a los receptores tipo Toll-4 precipita el desencadenamiento de esta vía de señalización y la activación de células endoteliales, que culmina con un estado protrombótico generado por la expresión de moléculas de adhesión intracelular 1, moléculas de adhesión vascular celular 1, selectina E, aumento del factor tisular e incremento de citocinas proinflamatorias como la interleucina 1 y el factor de necrosis tumoral. Por otro lado, las plaquetas son también activadas por este complejo antígeno-anticuerpo a través del receptor de lipoproteína de baja densidad relacionado con la proteína 8 y el receptor adhesivo plaquetario de la glucoproteína Ibα, llevando a un aumento en la producción de tromboxano A2 [8][9][10] .…”
Section: Discussionunclassified